2002
DOI: 10.2174/0929867023370077
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cysteine Residues of Biomolecules: New Approaches for the Design of Antiviral and Anticancer Drugs

Abstract: Modification of cysteine (Cys) residues in proteins, due to (i) the participation of the thiol moiety of this amino acid in oxido-reductions reactions; (ii) its ability to strongly coordinate transition metal ions; or (iii) its nucleophilic nature and facile reaction with electrophiles, may be of critical importance for the design of novel types of pharmacological agents. Application of such procedures, recently led to the design of novel antivirals, mainly based on the reaction of zinc finger proteins with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 80 publications
(228 reference statements)
1
33
0
Order By: Relevance
“…Thus, selectivity of adduction is governed by both the recipient nucleophile and the chemistry of the adducting electrophile. Likewise, Cys-239 in tubulin is preferentially alkylated by anticancer drugs, including the colchicines, Vinca alkaloids, rhizoxin/maytansine, and taxanes (Jordan et al, 1998;Shan et al, 1999;Kavallaris et al, 2001;Casini et al, 2002;Scozzafava et al, 2002), and carbonic anhydrase III, which contains five cysteine residues, is selectively alkylated at Cys-186 by acrylonitrile (Nerland et al, 2003). Cysteine thiols are clearly common targets of reactive electrophilic metabolites and endogenous electrophiles, including lipid-derived ␣,␤-unsaturated aldehydes, such as 4-hydroxynonenal (4-HNE) and 4-oxononenal, and reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, selectivity of adduction is governed by both the recipient nucleophile and the chemistry of the adducting electrophile. Likewise, Cys-239 in tubulin is preferentially alkylated by anticancer drugs, including the colchicines, Vinca alkaloids, rhizoxin/maytansine, and taxanes (Jordan et al, 1998;Shan et al, 1999;Kavallaris et al, 2001;Casini et al, 2002;Scozzafava et al, 2002), and carbonic anhydrase III, which contains five cysteine residues, is selectively alkylated at Cys-186 by acrylonitrile (Nerland et al, 2003). Cysteine thiols are clearly common targets of reactive electrophilic metabolites and endogenous electrophiles, including lipid-derived ␣,␤-unsaturated aldehydes, such as 4-hydroxynonenal (4-HNE) and 4-oxononenal, and reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it may be argued that disulfiram is akin to the failed first-generation modulators of Pgp, which were originally developed for other disease conditions and for reversing MDR only at relatively high concentrations. However, the extremely low toxicity of disulfiram (Chick, 1999) coupled with the fact that sulfhydryl-reacting agents, despite their apparently unspecific mode of action, provide useful drugs against human diseases (Yakisich et al, 2001;Scozzafava et al, 2002) distinguishes it from other first-generation MDR modulators. Also, disulfiram has been in clinical use for several decades and has a well-documented pharmacology.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to activating intracellular oxidant stress pathways, mass spectrometry (MS) analysis has recently revealed that brief exposure to K3 can result in arylation of the singular cysteine residue (Cys110) within histone H3.3/H3 [16]. Earlier studies had shown that brief treatment of ER-expressing breast cancer cells in culture with K3 also results in irreversible functional loss of ER-DNA binding [3], presumably due to the Michael addition of either the quinone or hydroquinone form of K3 to one or more nucleophilic groups within the ER-DBD [17,18]. However, analytical and structural studies of chemical modifications within the ER-DBD remain challenging, given the much lower abundance of endogenous ER relative to proteins like histone H3.3/H3, even when ER is markedly overexpressed in human breast cancer cells.…”
mentioning
confidence: 99%